The Role of Corporate Social Responsibility Perceptions in Brand Equity, Brand Credibility, Brand Reputation, and Purchase Intentions - Shu Wang (MDPI AG, 2021)
Corporate social responsibility (CSR) is becoming one of the most critical challenges that firms must address to survive in the competitive market. This study investigates the impact of customers’ CSR perceptions on their purchase intentions as mediated by brand equity, brand credibility, and brand reputation in order to identify the benefits of CSR integration for business development. The study employs a quantitative approach to collect data from customers who purchase cosmetics through an online survey. PLS-SEM software is used to analyze the data from the 380 responses. The results indicate that customers’ perceptions of the CSR of a firm affect their intention to purchase its brands in the future. Brand equity, brand credibility, and brand reputation mediate the impact of CSR perceptions on purchase intentions. Since previous studies have not employed a comprehensive approach to verifying the influence that CSR exerts through brand credibility, brand reputation, and brand equity, the results provide an essential reference for academics who conduct empirical research on the subject. This paper is also particularly beneficial for marketers and managers who wish to develop marketing strategies and brand management techniques that boost business efficiency.